1989
DOI: 10.1002/j.1939-4640.1989.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Receptors in Human Seminal Vesicles: Identification, Pharmacologic Characterization, and Comparison with the Vasopressin Receptors Present in the Human Kidney

Abstract: Because of the presence of a high density of vasopressin receptors in the epithelial cells of porcine seminal vesicles similar to the V2 vasopressin receptors of renal tubules, human seminal vesicles and kidney were investigated using quantitative binding and adenylate cyclase studies. Tissues were obtained at surgery from 17 patients with urologic diseases. A homogeneous class of vasopressin binding sites have been found in both seminal vesicles and renal medulla. However, the vasopressin receptors present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The K¿ for binding (2.5 nM) is comparable with that reported in other tissues (Jard, Lombard, Marie & Devilliers, 1987;Maggi, Baldi, Genazzani et al 1989) and is close to the EC5o value reported for secretion of insulin from normal mouse islets (Gao et al 1990). Although the value is higher than plasma levels of vasopressin (Schrier, Berl & Anderson, 1979), the existence of high concentrations of vasopressin in the pancreas (Amico, Finn & Haldar, 1988) suggests a possible local action of the hormone.…”
Section: Discussionsupporting
confidence: 86%
“…The K¿ for binding (2.5 nM) is comparable with that reported in other tissues (Jard, Lombard, Marie & Devilliers, 1987;Maggi, Baldi, Genazzani et al 1989) and is close to the EC5o value reported for secretion of insulin from normal mouse islets (Gao et al 1990). Although the value is higher than plasma levels of vasopressin (Schrier, Berl & Anderson, 1979), the existence of high concentrations of vasopressin in the pancreas (Amico, Finn & Haldar, 1988) suggests a possible local action of the hormone.…”
Section: Discussionsupporting
confidence: 86%
“…be considerable higher in many other species including human (47,48). Interestingly, maximum increases in intracellular cAMP levels induced by the V2R agonist dDAVP were reduced by about 50% in IMCD tubule suspensions prepared from kidneys of V2R +/-mice (Figure 5), providing a molecular correlate for the XNDI phenotype observed with the V2R +/-mutant mice.…”
Section: Figurementioning
confidence: 90%
“…The major peripheral biological effects of AVP are antidiuretic and vasopressor activity ( 1), whereas AVP may also be involved in sexual arousal ( 4). In humans, receptors for AVP have been described on platelets ( 5), in kidney and seminal vesicles ( 6). Furthermore, AVP neurones of the SON were shown to be activated in ageing, also in Alzheimer’s disease ( 7).…”
mentioning
confidence: 99%